Edukasi Penentuan Harga Jual Produk Rumahan - Ratnaningrum, Ratnaningrum; Susilowati, Heni; Hargyatni, Titin; Kusumaningtyas, Dhevi Dadi; Hidayat, Erwan Nur; Sulistyowati, Pemilia (Lembaga Dongan Dosen, 2023)
MSME business actors often set the selling price of household products incorrectly because the selling price of goods is only based on the owner's assumptions, not based on calculations and accounting rules. As a result, many micro businesses experience losses due to incorrect sales price assessments so that their sales income is not enough to cover all production costs. PKK women who manage household businesses sometimes lack knowledge about how to correctly assess the selling price of their goods. Therefore, the aim of this community service activity is to educate PKK cadres in Teras Boyolali sub-district about the basics of determining product selling prices in accordance with cost accounting principles and the importance of using cost accounting skills in micro businesses. In this way, PKK women are expected to be able to determine the selling price using the cost-plus pricing method. This approach is popular because it is easier for beginners and quite useful for setting selling prices appropriately.